Detection of immunoreactive proteins of Escherichia coli, Streptococcus uberis, and Streptococcus agalactiae isolated from cows with diagnosed mastitis - Dobrut, Anna; Wójcik-Grzybek, Dagmara; Młodzińska, Agata; Pietras-Ożga, Dorota; Michalak, Katarzyna; Tabacki, Aleksander; Mroczkowska, Urszula; Brzychczy-Włoch, Monika (Frontiers in Cellular and Infection Microbiology, 2023)
Mastitis is a widespread mammary gland disease of dairy cows that causes severe economic losses to dairy farms. Mastitis can be caused by bacteria, fungi, and algae. The most common species isolated from infected milk are, among others, Streptococcus spp., and Escherichia coli. The aim of our study was protein detection based on both in silico and in vitro methods, which allowed the identification of immunoreactive proteins representative of the following species: Streptococcus uberis, Streptococcus agalactiae, and Escherichia coli. The study group included 22 milk samples and 13 serum samples obtained from cows with diagnosed mastitis, whereas the control group constituted 12 milk samples and 12 serum samples isolated from healthy animals. Detection of immunoreactive proteins was done by immunoblotting, while amino acid sequences from investigated proteins were determined by MALDI-TOF. Then, bioinformatic analyses were performed on detected species-specific proteins in order to investigate their immunoreactivity. As a result, we identified 13 proteins: 3 (molybdenum cofactor biosynthesis protein B, aldehyde reductase YahK, outer membrane protein A) for E. coli, 4 (elongation factor Tu, tRNA uridine 5-carboxymethylaminomethyl modification enzyme MnmG, GTPase Obg, glyceraldehyde-3-phosphate dehydrogenase) for S. uberis, and 6 (aspartate carbamoyltransferase, elongation factor Tu, 60 kDa chaperonin, elongation factor G, galactose-6-phosphate isomerase subunit LacA, adenosine deaminase) for S. agalactiae, which demonstrated immunoreactivity to antibodies present in serum from cows with diagnosed mastitis. Thus, they can be considered potential targets in innovative rapid immunodiagnostic assays for bovine mastitis, however due to the limited number of examined samples, further examination is needed.